Microbial Aspect of GMP in Manufacture of Homoeopathic Medicines (Homoeopathy for All, 2022)
The manufacturing of homoeopathic medicines is one of the most highly regulated and rigorously controlled as per schedule M1 and different rules in the drug and cosmetic act and rules. In order to gain a manufacturing Licence, the manufacturer must prove to the regulatory authorities that not only is the product itself safe and effective, but that all aspect of the proposed manufacturing processes comply with the highest safety and quality standards various elements contribute to the safe manufacturer quality homoeopathic medicines such as:
Keywords: elements; quality homoeopathic; manufacturer